Food security and fruit and vegetable consumption among preschoolers: an exploratory study during the COVID-19 pandemic - Segui, Erick Martinez; Castro, Adriana Garcia Peloggia de; Silva, Jacqueline Tereza da; Collese, Tatiana Sadalla (O Mundo da Saúde, 2023)
Studies that assess food insecurity and its association with the consumption of fruits, legumes, and vegetables (FLV) can help identify groups and risk factors of inadequate food consumption, in order to propose assertive nutritional interventions. The aim of this study was to describe FLV consumption by children in different food security situations. This is an exploratory cross-sectional study, conducted with parents/guardians of 44 children from zero to four years old. The short version of the Brazilian Food Insecurity Scale and a Food Frequency Questionnaire were applied to parents/guardians via a telephone interview. The children were 2.6 years old on average, 56.8% were female, 67.5% were eutrophic, and 70.5% of the families were in a situation of food insecurity. For households in a situation of food security, the median consumption of FLV was 213.4 g/day (P25=97.89; P75=425.91). As for those in a situation of food insecurity, the median FLV was 105.4 g/day (P25=33.58; P75=205.16). It was concluded that the consumption of FLV by children from families in a situation of food security is higher than that of children in a situation of food insecurity, who are strongly influenced by the offer of cheap food with low nutritional quality. Public policies are needed to favor the guarantee of access to FLV of quality and at an affordable cost for all families.